The Relationship between Oil Prices and Inflation in Oil İmporting Countries (1980-2022) - Kudabayeva, Lyazzat; Abubakirova, Aktolkin; Zurbayeva, Aliya; Mussaeva, Gulnar; Chimgentbayeva, Gulbakyt (International Journal of Energy Economics and Policy, 2024)
The increase in the price of oil, which is an important input in production, decreases the level of output, causes cost inflation and generally affects the economy negatively. In oil-importing countries, it leads to an increase in costs and a decrease in competitiveness in international trade, thus negatively affecting the balance of payments. The aim of this research is to investigate the relationships between oil price and inflation by using quarterly data between 1980Q1:2022Q4 in oil importing countries. In addition, it is aimed to determine the contribution of the GDP and unemployment rate variables, which are widely used in explaining inflation, as well as the inflationary effects of oil prices. According to the results of the study, the effect of oil prices on inflation differs from country to country. It is observed that Italy and France are the most affected countries.